Photonic Generation of Triangular Pulses Based on Phase Modulation and Spectrum Manipulation - Yongsheng Gao; Aijun Wen; Wenya Liu; Huixing Zhang; Shuiying Xiang (IEEE Photonics Journal)
A photonic triangular pulse generation method based on spectrum manipulation of phase-modulated signals is proposed and experimentally demonstrated. A light wave is first phase modulated by a sinusoidal signal to generate optical sidebands. Then, the optical spectra are manipulated by attenuating the optical carrier and one of the first-order sidebands with the same suppression ratio. By choosing a proper modulation index, a full-duty-cycle triangular pulse train with a repetition rate equal to the frequency of the drive signal can be generated. To improve the practical feasibility and the repetition-rate tunability, the spectrum manipulation is realized using a Sagnac loop and a fiber Bragg grating (FBG). In the experiment, four full-duty-cycle triangular pulse trains with different repetition rates (3–6 GHz) are successfully generated, and the repetition rate can be further improved if larger bandwidth measuring instruments are used. In addition to the large and tunable repetition rate, the proposed scheme also features the advantages of simple structure, low cost, and freedom from bias drift.